The Role of Schools in Improving Children's Physical Motor Development in Learning - Slamet Waluyo; Yahya Sudarya (UM Purwokerto Press, 2023)
This study uses a literature review method by examining several articles and books. This study aims to determine the physical-motor development of children at SD Negeri 2 Wlahar and to describe the role of the school in improving children's physical-motor development. In addition to reviewing the literature, data collection in this study used observation, interviews and documentation techniques. In addition, this study uses a descriptive research approach which has the aim of explaining phenomena or events that exist in the field. The subjects of this study were 68 students in grades 4 - 6. The data analysis technique in this study used analysis before going to the field and analysis in the field using the Miles and Huberman model which includes data reduction, data display and conclusion drawing. Based on the results of the research conducted, it can be explained that in the learning process it can be seen that all students have different motor-physical developments and these developments continue and change according to student learning activities. Schools have an important role in improving the development of the motoric physiology of their students.